Conductivity studies of MG-30 composite polymer electrolytes / Nur Shahida Azib - Azib, Nur Shahida (2010)
In this study, composite polymer electrolyte comprised of MG-30 polymer host, Zink chloride salt (ZnCk), propylene carbonate (PC) plasticizer and Aluminium oxide (AI2O3) filler are prepared using the solution casting technique. Impedance spectroscopy technique was carried out in order to determine the electrical conductivity value. Analysis showed that the higher conductivity was 2.08X10"4 S/cm is achieve when 20 wt% AI2O3 is introduced into the system containing l.Og MG-30 doped with 60 wt% ZnCfe.